Synthesis and Identification of Complexes of [1, 2-diphenyl -2- (pyrazin -2- ylimino)- ethanone oxime] with Some Metal Salts - A.N. Al-Jeboori; T.H . AL-Noor; R.L. Sadawi (College of Pharmacy / Mustansiriyah University, 2009)
Aim of this work is synthesis and characterization of bidentate Oxime ligand (HL) [1,2-diphenyl-2-(pyrazin-2-ylimino)-ethanoneoxime]. This ligand was prepared by reacting of 2-aminopyrmidine (A) with benzylmonooxime (B) under reflux in methanol and drops of CH3COOH gave the ligand (HL).fig(1) .The prepared ligand were characterized by I.R, U.V-vis spectra and melting point.The ligand were reacted with some metal ions under reflux in methanol with (1:1) ratio gave complexes of the general formula: [M (HL)], Where: M= MnII, FeII, CoII, CuII, ZnII, CdII, NiII, and HgII. These complexes were characterized by (A.A), chloride content I.R, U.V-vis spectra, molar conductivity and melting point. The molar conductance showed that, all complexe are non-electrolyte.